Pengembangan Multimedia Pembelajaran Berbasis Saintifik Mengunakan Adobe Flash Professional CS6 untuk Siswa SD - Afreni Hamidah; Nazurty (Jurnal Gentala Pendidikan Dasar, 2021)
Multimedia learning can be used to help facilitate the process and understanding in learning, and increase interest in learning, this is because it is presented with attractive pictures and animations, accompaniment music and voice presenters, short duration of time, using a scientific approach in accordance with the revised 2013 curriculum. This study aims to: 1) Develop a scientific-based learning multimedia design for elementary students 2). Knowing the feasibility of scientific-based learning multimedia for elementary students, 3). The response of teachers and students to learning media as a result of development. This type of research is research and development (R & D). The development design model refers to the 4D model with 4 stages, namely: Define, Design, Development, and Disseminate. The research instruments used were observation sheets and questionnaires. The data obtained are in the form of qualitative and quantitative data. Qualitative data is in the form of comments and suggestions from experts/validators of media and materials. Quantitative data were obtained from questionnaire scores with a Likert range scale. The feasibility of the product is assessed based on the feasible and very feasible product category with a percentage between 80-100%. Media that are already feasible are tested on small group and large group test subjects. The results of the assessment from media experts got 92% with very valid criteria, and from material experts it was 86.7% with very valid criteria. The results of the feasibility/practical assessment through student response questionnaires at the trial stage show very practical criteria